Jerzego Giedroycia idea ULB – geneza, założenia, próby realizacji. Zarys problematyki - Waingertner, Przemysław (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2015)
Jerzy Giedroyc (1906–2000), in the Second Republic of Poland the ministerial official and, above all, ideologue and leader of the student youth organization of the conservative movement and the originator neo-conservative periodical “Bunt Młodych” and “Polityka”, in the years of World War II in the Second Polish Corps, is known above all as one of the most important figures of Polish emigration after the World War II – organizer of the Literary Institute in Paris, creator of the periodicals “Kultura” and “Zeszyty Historyczne” and the publisher of the greatest writers of Polish emigration. Along with his political allies and associates (Juliusz Mieroszewski, Józef Łobodowski, Konstanty Jeleński and Jerzy Stempowski) became famous as the creator and promoter of the idea of “ULB” – historic reconciliation and cooperation between the Poles, Lithuanians, Ukrainians and the Belarussians, the aim of which was to be the weakening of the Soviet domination of Eastern Europe and creating of the grounds for close co-operation of Ukraine, Lithuania and Belarus with Poland after the fall of the Soviet Union. It would be the guarantee stability in the region, the antidote to the revival of Russian imperialism, as well as a pillar of the position of the states of “ULB” in Europe.